Pengaruh Konsentrasi Larutan Sukrosa dan Waktu Perendaman Terhadap Kesegaran Bunga Potong Oleander (Nerium oleander L.) - Eny Yuniaty; Muhammad Alwi (Biocelebes, 2011)
The study of "The Effect of Solvent Preservative Against Security To Save Oleander Flowers (Nerium oleander L.)" was held from March to April 2011 which aims to identify and study the effect of preservative solutions on postharvest quality of cut flowers Oleander (Nerium oleander L.). The research method used is an experiment with 14 treatments and 3 replications. The design used was the design (CRD) with factorial pattern factor of sucrose concentration and immersion time. The results showed that the resistance to keep, the number of blooming flowers, flowers wither, and the volume of water absorption is best at a concentration of 5% with 2 hours soaking time compared with other treatments.